2018
DOI: 10.21608/ejbo.2018.2114.1138
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Habitats on the Chemical Consituents of Codium Tomentosum

Abstract: T HE CURRENT study was conducted to assess the influence of different harvesting site (habitat) on the chemical constituents of Codium tomentosum Stack collected from two different sites on the coast of Egypt (Mediterranean [M] and Red [R] Seas). The current results showed that, salinity and temperature of the Red Sea is relatively higher than those of the Mediterranean one. Additionally, results indicated significant differences in the biochemical profiles of Codium between the two sampling sites. The total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Jormalainen and Honkanen (2008) demonstrated that concentrations of algal phenolic compounds vary according to habitat, season and local environmental factors such as salinity, light, and nutrient availability. Mansour et al (2018) found that change in salinity level between Red Sea and Mediterranean Sea doesn't induce a significant difference in the total phenol content of Codium tomentosum. However, Connan and Stengel (2011) reported a negative relationship between phenolic levels and salinity increase in some species of brown algae.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Jormalainen and Honkanen (2008) demonstrated that concentrations of algal phenolic compounds vary according to habitat, season and local environmental factors such as salinity, light, and nutrient availability. Mansour et al (2018) found that change in salinity level between Red Sea and Mediterranean Sea doesn't induce a significant difference in the total phenol content of Codium tomentosum. However, Connan and Stengel (2011) reported a negative relationship between phenolic levels and salinity increase in some species of brown algae.…”
Section: Resultsmentioning
confidence: 95%
“…The free radical scavenging activity (DPPH%) of the methanol extracts of both Dictyota dichotoma and Sargassum dentifolium behaves similarly as the higher activity in both macroalgae were recorded in Hurghada (56.63%, 64.47%, respectively), while the lower activities were recorded in the samples collected from Abu-Qir (51.43%, 59.69%, respectively). Mansour et al (2018) referred the increased antioxidant capacity in the samples of Codium tomentosum collected from Red Sea to the relative increase in its salinity and temperature, as compared with values recorded in Mediterranean Sea, which considered as stimulator to the alga to produce different secondary metabolites to overcome the effect of these stressors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the phylogenetic pathway, marine organisms were able to modify their metabolism and produce an array of compounds to avoid this type of oxidizing damage. Additionally, algae have evolved protective mechanisms against oxidation that promote the production of metabolites to re-establish cell metabolism, which can modify the antioxidant system to correct cellular redox balance [18,52]. Products of algal metabolism have been the target of multiple studies due to their bioactivity [2,4,11,12,46].…”
Section: Discussionmentioning
confidence: 99%
“…Algal metabolism is dependent on several factors that influence their metabolome: physiological status, presence/absence of epiphytic organisms, growth habitat, environmental conditions (e.g., temperature, light, and nutrients) or seasonal fluctuations [14][15][16][17]. In order to survive under shifting environments, cells promote metabolic adaptations according to environmental growth conditions and habitats [18]. The understanding of this chemoplasticity is important for the valorization of algae in different applications.…”
Section: Introductionmentioning
confidence: 99%